POLICY IMPLEMENTATION BPJS HEALTH AT PUSKESMAS PATLEAN, NORTH MABA DISTRICT, EAST HALMAHERA DISTRICT - KAOTJI, NELSA NOVIANA; TULUSAN, FEMMY; MAMBO, RULLY (Sam Ratulangi University, 2018)
Abstract: Policy Implementation social security organizing body (BPJS) health, is an important in the world of health. Through Policy Implementation BPJS health.Is expected to help people who are less able in the world health, especially in terms of treatment a hospital or puskesmas.success of policy implementation bpjs heatlh, depending on the aspect of communication, resources, disposition, bureaucratic structure. If the four variables support each other, then policy implementation BPJS heatlh can be achieved effectively and on target. The purpose of policy implementation BPJS heatlh is to achieve the degree of the poor or economically weak in the needs of treatment. On of the efforts made by the government is to take health card BPJS program.and by providing facilities and infrastructure at heatlh center for the implementation of health on target. The purpose of this study is to know Policy Implementation BPJS Health At Puskesmas . The benefits of this research are to provide input to the Health Center or stakeholders within Policy Implementation BPJS Health At Puskesmas Patlean, North Maba District, East Halmahera District. The method used is qualitative method, with type of descriptive approach and research location patlean village North Maba District, East Halmahera District. Data collection is done by observation and in-depth interview to informant. Based on the results of the study there are several factors that must be corrected communication, resources, disposition, bureaucratic structure.so inside Policy Implementation BPJS Health At puskesmas goes according to expectations.Based on the results of the study there are several factors that must be corrected : communication, tesources, disposition, and bureaucratic structure. So that in the implementation of the policy BPJS the health program at the puskesmas goes according to expectations.Keywords : policy implementation, healt social security